2021
DOI: 10.20291/1815-9400-2021-2-40-43
|View full text |Cite
|
Sign up to set email alerts
|

Organization of transportation by tank cars of solidified petroleum fuels with transmission through field pipelines in low temperature conditions

Abstract: The method of unloading and reloading solidified oil fuels, with the use of pipelines made according to temporary technological schemes, produced in winter, is considered. Cooling of solidified fuels is accompanied by a sharp increase in their viscosity, which makes pipeline transmission impossible. In fire hazard, it is proposed to produce continuous heating of the pumped fuel using devices based on low-temperature combustion of propane-butane mixture on the surface of the catalyst carried out at fire-safe te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It can be concluded that when TGC is suppressed, a liquid petroleum product will cool down as a quasisolid body by molecular thermal conductivity at λ VPP of about 0.12 W/m°C, and the temperature distribution in it will correspond to the picture shown in Fig. 2 [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Evaluation Of the Results Of Hydrodynamic Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that when TGC is suppressed, a liquid petroleum product will cool down as a quasisolid body by molecular thermal conductivity at λ VPP of about 0.12 W/m°C, and the temperature distribution in it will correspond to the picture shown in Fig. 2 [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Evaluation Of the Results Of Hydrodynamic Calculationsmentioning
confidence: 99%
“…Options for the use of tank wagons with a steam heating casing and tanks for light general-purpose petroleum products are being considered [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%